The prevalence of obstructive sleep apnea in symptomatic patients with syndromic craniosynostosis. Issue 2 (February 2016) - Inverso, G.; Brustowicz, K.A.; Katz, E.; Padwa, B.L.
Abstract: The reported prevalence of obstructive sleep apnea (OSA) in patients with syndromic craniosynostosis (SCS) varies due to inconsistent definitions of OSA, lack of uniform diagnostic testing, and different mixes of syndromic diagnoses. The purpose of this study was to determine the prevalence of OSA in symptomatic patients with SCS, and to determine whether this differs by phenotypic diagnosis. A retrospective cohort study of children with SCS was conducted. The primary outcome was presence of OSA diagnosed by polysomnography. The prevalence of OSA was calculated and stratified by diagnosis to compare differences in prevalence and severity (mild, moderate, or severe). The prevalence of OSA in symptomatic patients was 74.2%. Patients with Apert syndrome had the highest prevalence (80.6%), followed by Pfeiffer, Crouzon with acanthosis nigricans, and Crouzon syndromes (72.7%, 66.7%, and 64.7%, respectively). Severe OSA was most common in patients with Pfeiffer syndrome (45.5%), while patients with Apert and Crouzon syndromes were more likely to have moderate OSA (29.0% and 23.5%, respectively). Given that 56.4% of patients with SCS are symptomatic and that 74.2% of these symptomatic patients have OSA, it is recommended that a screening level I polysomnography be part of the clinical care for all patients with SCS.